Lipid production from bioremediation of palm oil mill effluent - Athoillah, Ahdyat Zain; Ahmad, Farah (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Palm oil mill effluent (POME) is a by-product from palm oil production. As a consequence of the boost of palm oil production, POME generation also increases. It can be considered as the harmful waste if it is released without any treatment. Meanwhile, POME contains various types of microorganism and a big proportion of the organic matter. Therefore palm oil mill effluent has the potential to be a source of isolation of novel fungal strains and raw material for low cost lipid production. Oleaginous microorganisms are microorganisms that are able to accumulate more than 20 wt% lipid in its cell body. This study aims to isolate potential oleaginous fungi from POME and to evaluate the ability of lipid production capacity of the purified isolates and three commercial strains (Aspergillus niger, Aspergillus oryzae and Rhizopus spp). POME was converted into lipid via oleaginous fungi for biodiesel production. In this study, two fungal strains were successfully isolated from POME. The isolation was performed by spreading the diluted POME onto potato dextrose agar. Glucose-rich basic media and POME media were used as the source of carbon substrates of these fungal strains. Upon completion of the fermentation, the biomass was then harvested to extract its intracellular lipid. This study provides a basis for microbial oil production by fungi from POME as main feedstock.